Cover Feature: Optically Triggered Control of the Charge Carrier Density in Chemically Functionalized Graphene Field Effect Transistors (Chem. Eur. J. 29/2020). Issue 29 (23rd April 2020) - Tang, Zian; George, Antony; Winter, Andreas; Kaiser, David; Neumann, Christof; Weimann, Thomas; Turchanin, Andrey
Abstract : Non‐destructive functionalization of devices based on two‐dimensional materials via the assembly of van der Waals heterostructures with atomically thin molecular nanosheets is reported. The field‐effect transistor depicted in the cover consists of graphene and ∼1 nm thick molecular nanosheet with grafted azo‐benzene molecules. Irradiation of this device with UV/VIS light results in the conformational changes of azo‐benzene, which induces modification of the charge carrier concentration in the graphene. In this way the transport characteristics are tuned by an optical stimuli. More information can be found in the Communication by A. Turchanin et al. on page 6473 .